Synthesis, Characterization and Biological Activities of Novel Chiral Bis 1,2-diolcarbothioamides - Karatepe, Arzu; Koparır, Pelin; Daştan, Taner; İnci, Şule; Keser, Serhat; Çetin, Ahmet (Niyazi BULUT, 2024)
2,2'-[(2R,3R)-2,3-dihydroxy-1,4-dioxobutane-1,4-diyl]bis(N-aryl-alkylhydrazine-1-carbothioamide (T1–5) were obtained by the interaction of (2R,3R)-2,3-dihydroxybutanedihydrazide (1) with five different isothiocyanate alkyl(aryl) derivatives. The structures of the final compounds were confirmed by elemental analyses, FT-IR, ¹H-NMR and ¹³C-NMR. The antioxidant, antimicrobial and anticancer properties of the synthesized compounds were also investigated. Three of the triazole derivatives with p-tolyl, benzyl and phenyl substituents (T3–5) displayed good antioxidant and anticancer activity in comparison to the standards.
Keywords: Physical Chemistry (Other); Fiziksel Kimya (Diğer)